2017
DOI: 10.1017/inp.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Plant Community Effects and Genetic Diversity of Post-fire Princess Tree (Paulownia tomentosa) Invasions

Abstract: Many naturalized populations of the invasive tree princess tree exist in North America, yet little research has quantified its effect on native plant communities. A series of recent wildfires in the Linville Gorge Wilderness Area (LGWA) promoted multiple large-scale princess tree invasions in this ecologically important area. To measure community shifts caused by these princess tree invasions across burn areas, we sampled vegetation in paired invaded and noninvaded plots in mature and immature invasions within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Invasive species can indirectly affect native plants by changing habitat conditions and ecological processes, or directly by competing with native species for resources and space [69]. One study [27] found that fire promotes the invasion of paulownia but is not necessary for subsequent recruitment, and its presence reduces the native plant diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive species can indirectly affect native plants by changing habitat conditions and ecological processes, or directly by competing with native species for resources and space [69]. One study [27] found that fire promotes the invasion of paulownia but is not necessary for subsequent recruitment, and its presence reduces the native plant diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Fire often acts as a large-scale disturbance that promotes recruitment of some invasive plants [23][24][25], and fire appears to promote invasions of paulownia [26]. Paulownia was found to invade two separate areas that experienced wildfire in the Linville Gorge Wilderness Area, North Carolina, and the native plant communities changed as a result of its invasion [27].…”
Section: Introductionmentioning
confidence: 99%